ASPEK HUKUM PERSAINGAN USAHA TIDAK SEHAT PADA PEDAGANG RITEL - Rini Novita; Diana Lubis; Cut Nurita (Universitas Islam Sumatera Utara, 2023)
One of the problems encountered when talking about the business climate is unfair competition. Basically the business world is concerned with or longs for big profits in its business sector. The form of business competition in retail traders is that business actors set prices below the market price that should be, between franchise minimarkets one with another vying to set prices far below the market price. The existence of price competition carried out by the franchised minimarkets can have a negative impact on traditional business actors in the vicinity of these locations, namely traditional traders losing consumers. The legal remedy for retail traders in dealing with conflicts between retail traders is to make a complaint or report to KPPU. Parties who suffer losses as a result of violations of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition may report in writing to KPPU with complete information and include the identity of the complainant.Keywords: Competition Unfair, Business, Retail.